Introduction to the Typical Three-Body Problem Periodic Orbit and its Application in Deep Space Exploration - Wang, Qianen (Transactions on Computer Science and Intelligent Systems Research, 2025)
This paper focuses on periodic orbits in the three-body problem, systematically expounding the basic concepts of the three-body problem, classifying typical three-body problems and restricted three-body problems, and defining, characteristics and formation mechanism of periodic orbits. By analyzing typical orbital types such as special solutions to Lagrange points, low-energy periodic orbits, and resonant periodic orbits, combined with the application of the Queqiao satellite in the L2 halo orbit of the Chang'e-4 mission, the core value of periodic orbits in deep space exploration is verified. The study also explores technical methods for simulating and verifying periodic orbits, points out the limitations of current research in dealing with sudden gravitational interference, model simplification errors, and high-dimensional orbit searches, and proposes improvements that combine artificial intelligence, quantum computing, and refined gravitational field models. Finally, the application prospects of periodic orbits in future deep space missions such as Mars exploration and asteroid sample return are envisioned, aiming to provide a reference for understanding the theoretical significance and engineering value of periodic orbits.
Keywords: Astronomy; physics; three-body problem; universe.